Surveying the Effect of Work-Life Balance on Quality of Life (Case Study : Hospitals of Sanandaj) (Tehran University of Medical Sciences, 2015)
Background: This study is aimed at investigating the effect of work-life balance in hospitals of Sanandaj. Work-life balance includes different aspects such as : family, work,leisure and personal growth. Moreover,the quality of life had been assessed by physical, mental, social, and environmental dimensions of health. Materials and Methods: The statistical population includes personnel of hospitals of Sanandaj including doctors, nurses, office employees, technicians and guards. 150 individuals had been selected among mentioned population by using cluster sampling and Cochran formula as sampels. The data were analyzed using structural equations and AMOS18 and SPSS20 softwares. Results:The results of this study showed that the main hypothesis of  work-life balance  among personnel of hospitals had an effect of 0.70 on the quality of their working life. Nevertheless , second  hypothesis titled as "The effect of holding the balance in family on quality of life" was rejected because its critical value was in the range of rejecting the hypotheses. Conclusion: Each three non-working dimension had an effect on the quality of life personnel which might be a result of the current economic downturn in Sanandaj.